Optimisation of Fertiliser Delivery Distribution from Distributor to Farmer Group Using Excel Solver in Tanjung Village - Hasanah, Uswatun; Halizah, Siti Nur (Journal of Computer Science Advancements, 2024)
Subsidised fertilisers are declared as goods that are monitored for distribution with a specific target, namely farmers. In the distribution process, the government cooperates with various components including the Ministry of Industry and Trade, the Ministry of Agriculture, the Ministry of State-Owned Enterprises and the Ministry of Home Affairs. At the same time, transportation and communication technologies continue to develop rapidly, such as mobile communications and the Internet, which drive the continuous development of the supply chain and technologies related to its regulatory management. This research aims to find out how to optimise the fertiliser transprortation Fertiliser Delivery Distribution and a series of fertiliser supply systems from Distributors to Farmer Groups Using Excel Solvers in Tanjung Village so as to provide better user control. The benefits of this research for distributors can help buffer distributor management to determine the quantity and time of delivery of subsidised fertiliser to official kiosks. The research method uses a case study which is a method of collecting and processing data through review / study of various research reports, flowsheets, research journals, as well as books and other relevant literature.